Understanding and controlling the glass transition of HTPB oligomers - Dossi, Eleftheria; Earnshaw, Jacob; Ellison, Laurence; Rabello dos Santos, Gabriella; Cavaye, Hamish; Cleaver, Douglas J. (Royal Society of Chemistry, 2021)
In this paper, we use a combination of experiment and simulation to achieve enhanced levels of synthetic control on the microstructure of the much-used binder material hydroxyl terminated polybutadiene (HTPB). Specifically, we determine the appropriate combination of initiator, temperature and solvent required to dial in the relative contents of trans, cis and vinyl monomeric units. When an alkylithium initiator (TBDMSPLi) is used, the vinyl content increases from 18% to >90% as the polymerization solvent is switched from non-polar to polar. Further, in non-polar solvents, the vinyl content increases from 18% to 40% with decreasing polymerization temperature. The glass transition temperature, Tg, is shown to be strongly affected by the microstructure, covering the very wide range of −95 °C to −25 °C. The Tg values of HTPB oligomers with high vinyl content are exceptionally high (−25 °C) and can be associated with their aliphatic backbones with pendant side-groups structures. The experimental indications that intramolecular degrees of freedom have a dominant effect on Tg are confirmed by Molecular Dynamics simulations. These simulations identify crankshaft flips of main-chain sub-sections as the key mechanism and relate this to the vinyl content; the frequency of these rotations increases by an order of magnitude, as the vinyl content is reduced from 90% to 20%. The generic mechanistic understanding gained here into what constitutes a “good binder” material is readily transferrable to the potential identification of future candidate systems with very different chemistries.